PROTECTION RELIGIOUS RIGHTS FOR CHILDREN BASED ON ISLAMIC LAW AND LEGISLATION IN INDONESIA - Mukhsin Nyak Umar; Nurdin Bakry; Iwan Alfitra (Universitas Islam Negeri Ar-Raniry, 2023)
This research discusses the importance of the application of religious rights protection for children based on the perspective of Islamic Law and legislation in Indonesia. Religious rights are human rights that must be guaranteed and protected, especially for children as a vulnerable group. This study examines the norms of Islamic Law that emphasize the need to protect children's religious rights from an early age. The study also analyzes the relevance between Islamic teachings and national legal provisions related to the protection of children's religious rights. This understanding is directed at efforts to prevent potential violations of religious rights that may occur in the context of everyday life. In addition, this study evaluates the effectiveness of existing legal and regulatory mechanisms in Indonesia in providing guarantees and protection of children's religious rights.The research method used includes analysis of legal literature, normative studies, The results of this study are expected to contribute to an in-depth understanding of the implementation of religious rights protection for children in the context of Islamic law and legislation in Indonesia. The implications of the findings of this research can provide a basis for the development of more effective policies in ensuring children's religious rights in the future.